Does food insecurity link to suicidal behaviors among in-school adolescents? Findings from the low-income country of sub-Saharan Africa - Festo K. Shayo; Paul S. Lawala (BMC Psychiatry, 2019)
Abstract Background Suicidal behaviors among adolescents is a major public health concern. Psychological factors have been extensively studied known risks linked to suicidal behaviors in the general population. However, the association between food insecurity and suicidal behaviors is less researched, particularly in low and middle-income countries. The present study sought to assess the link between food insecurity and suicide behaviors among in-school adolescents. Methods The present study was based on the secondary analysis of the first nationally representative sample of the 2014 Tanzania Global School-based Student Health Survey (GSHS). A total sample of 3,793 in-school adolescents was included in the present analysis. The primary independent variable was food insecurity while the dependent variables of interest were suicide ideation and suicide attempt. Chi-square χ2 and multivariate logistic regression were used to ascertain the measure of statistical association. In all analyses, a p < 0.05 was considered statistically significant. Results Of the 3,793 in-school adolescents, 254 (6·7%) were food insecure. A significantly large proportion of adolescents with suicidal ideation and suicidal attempt were food insecure than their counterparts, respectively. In the adjusted multivariate model, food insecure adolescents were more likely to have experienced suicidal ideation and suicidal attempt: [AOR; 1·8 95% C. I; 1·3–2·5] and [AOR; 2·4, 95% C. I; 1·7–3·3]; p < 0.001, respectively. Conclusion Food insecurity was an independent predictor of suicidal behaviors among in-school adolescents. An intervention that targets food security at the school level may protect adolescents of food insecure household from suicidal behaviors. Nevertheless, school-based mental health screening, evaluation, and promotion may be needed for adolescents with suicidal behaviors.